2008
DOI: 10.1021/jp803808e
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Valence Bond Mixing Configuration Diagrams to Hypervalency in Trihalide Anions: A Challenge to the Rundle−Pimentel Model

Abstract: The X(3)(-) hypercoordinated anions (H, F, Cl, Br, I) are studied by means of the breathing-orbital valence bond ab initio method. The valence bond wave functions describe the different X(3)(-) complexes in terms of only six valence bond structures and yield energies relative to the two exit channels, X(2) + X(-) and X(2)(-) + X(*), in very good agreement with reference CCSD(T) calculations. Although H(3)(-) is unstable and dissociates to H(2) + H(-), all the trihalogen anions are stable intermediates, Br(3)(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 59 publications
4
42
0
7
Order By: Relevance
“…Polyfluoride anions are of synthetic and theoretical interest, and their chemical bonding, stability, and properties have repeatedlyb een studied by quantum-chemical methods. [76,[79][80][81][82][83][84][85][86][87][88] At the coupled-cluster level (CCSD(T)/def2-ZVPP)t he reaction of free F À and F 2 to yield the free [F 3 ] À and [F 5 ] À ions is exothermicb yÀ116.6 and À131.9 kJ mol À1 ,r espectively. [34] By contrast, due to the relatively strong coulombic bonding interaction in M + [F] À ,t he formationo ft he M + [F 3 ] À and M + [F 5 ] À ion pairs is by far less favored.…”
Section: Polyfluoridesmentioning
confidence: 99%
“…Polyfluoride anions are of synthetic and theoretical interest, and their chemical bonding, stability, and properties have repeatedlyb een studied by quantum-chemical methods. [76,[79][80][81][82][83][84][85][86][87][88] At the coupled-cluster level (CCSD(T)/def2-ZVPP)t he reaction of free F À and F 2 to yield the free [F 3 ] À and [F 5 ] À ions is exothermicb yÀ116.6 and À131.9 kJ mol À1 ,r espectively. [34] By contrast, due to the relatively strong coulombic bonding interaction in M + [F] À ,t he formationo ft he M + [F 3 ] À and M + [F 5 ] À ion pairs is by far less favored.…”
Section: Polyfluoridesmentioning
confidence: 99%
“…It is concluded that the bonding mode of these hypervalent species and isoelectronic ones complies with Coulson's version of the Rundle-Pimentel model, but assisted by charge-shift bonding. The conditions for hypervalence to occur are stated.H À exchange reaction, lying 11 kcal mol À1 above the reactants, [8] although the isoelectronic F 3 À is stable. To quote Kutzelnigg, [9] "Whereas simple MO theory has no difficulty in describ-Scheme 1.…”
mentioning
confidence: 99%
“…H À exchange reaction, lying 11 kcal mol À1 above the reactants, [8] although the isoelectronic F 3 À is stable. To quote Kutzelnigg, [9] "Whereas simple MO theory has no difficulty in describ-Scheme 1.…”
mentioning
confidence: 99%
“…5 However, our distance agrees well with the result (2.945 Å) at the CCSD(T)/aug-cc-pVTZ-PP level (all orbitals are correlated) by Braïda and Hiberty. 23 The difference in bond lengths calculated with ostensibly the same methodology, not to speak of what would be obtained with different levels of calculation, serves in a way to set the theoretical equivalent of an error bar on a calculation. Figure 3) optimized using the CCSD(T)/AWCVTZ method.…”
Section: Equilibrium Geometries For MXmentioning
confidence: 99%